PELAKSANAAN SOSIALISASI PROGRAM ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) SEBAGAI UPAYA MEWUJUDKAN BUDAYA TERTIB LALU LINTAS DI KOTA PEKANBARU - Septika Ayu Putri; Zaili Rusli (Cross-border, 2022)
Technology is increasingly sophisticated and the number of vehicles is increasing, causing the number of cases of traffic violations on the highway to increase. In this case, the Police issued an innovation as a new measure in traffic order enforcement called ETLE (Electronic Traffic Law Enforcement). Electronic Traffic Law Enforcement (ETLE) is a traffic law enforcement system based on information technology that utilizes electronic devices, namely cameras that function to detect various kinds of traffic violations and display motorized vehicle data automatically using Automatic Number Plate Recognition (ANPR). a program to run effectively requires socialization to the community. Sub Directorate of Gakkum Ditlantas Riau Police is one of the agencies that play a role in disseminating the ETLE program in Pekanbaru City. This study uses a qualitative method with a descriptive approach where the data collection techniques used are interviews, observations, and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusions. The results of the research in the field stated that the socialization carried out by the Sub-Directorate of Gakkum Ditlantas of the Riau Police was not optimal, this was because there were still many people who did not know and understand the ETLE program. If the socialization is carried out optimally, it will have a good influence and will also create a culture of orderly traffic for road users, especially in Pekanbaru City with this ETLE program.